Complexity & Development 2.0: From Agreeing We Should Adapt to Creatin g the Conditions that Enable Adaptation - Ang, Yuen Yuen (2018)
The field of global development has reached a critical turning point. Almost gone is the mechanical, one-size-fits-all “good governance” par adigm of the past. In its place is a growing embrace of complexity and systems thinking. While this is an encouraging shift in the right dir ection, the discussion mostly ends by concluding that we should adapt. Yuen Yuen Ang urges that it’s time to take our conversation on “compl exity & development” to the next level: how to enable adaptation. Effe ctive adaptation doesn’t automatically arise just because we desire it —rather, it requires certain enabling conditions. In How China Escaped the Poverty Trap (2016), she introduces a generic complexity 2.0 fram ework that she terms “directed improvisation.” Effective adaptation, Y uen Yuen argues, requires a paradoxical blend of top-down direction an d bottom-up improvisation. Such a system can be created—and produce dr amatic results and adaptive solutions—even within a closed political r egime like China.